The Influence of Corporate Governance Perception Index, Profitability, and Company Size on Stock Value on Go Public Companies at CGPI Listed on the Indonesia Stock Exchange - Ika Swasti Putri; Siti Hayati Efi Friantin; Dino Aryanto (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This research aims to determine the impact of corporate governance perception index, profitability, and company size on the value of CGPI-listed companies listed on the Indonesian Stock Exchange for three years. The data used in this study are second-hand data. The data for this research comes from the company's 2017-2019 annual report for the observation period. Using purposeful sampling methods, samples were obtained from as many as 16 companies using data collection techniques. The data analysis methods used in this study are multiple linear regression analysis, classical hypothesis testing, and hypothesis testing. The results show that the impact of corporate governance perception index, profitability, and company size also affect stock value. The influence of the independent variable on the dependent variable is 37.7%, and the remaining 62.3% are affected by variables other than this study. For partial results, the influence of the Corporate Governance Perception Index and Profitability and has a significant positive effect on Share Value, while the size of the company has no significant positive effect on the value of the share.